Characterization of densification behavior and mechanical properties of solid electrolyte powders for all solid-state batteries - Lee, Seung-Yong; Han, Ji-Hoon; Gong, Hyun-Woo; Ahn, Jae-pyoung; Yi, Kyung-Woo; Cho, Young Whan (Royal Society of Chemistry, 2025)
A simple powder compression method was used to compare the mechanical properties of various argyrodite-type solid electrolytes. The Heckel plot's K values revealed differences in plastic deformation behavior, aligning qualitatively with nano-indentation test results.